2016
DOI: 10.4103/0366-6999.193459
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Propofol and Etomidate Exposure Enhance Inhibitory Synaptic Transmission in Hippocampal Cornus Ammonis 1 Pyramidal Neurons

Abstract: Background:Propofol and etomidate are the most important intravenous general anesthetics in the current clinical use and that mediate gamma-aminobutyric acid's (GABAergic) synaptic transmission. However, their long-term effects on GABAergic synaptic transmission induced by neonatal propofol or etomidate exposure remain unclear. We investigated the long-term GABAergic neurotransmission alterations, following neonatal propofol and etomidate administration.Methods:Sprague-Dawley rat pups at postnatal days 4–6 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…32 Interestingly, etomidate exposure during the same period (i.e., P4-P6) does not induce long-term alterations in IPSC frequency. 33 Collectively, these data, along with our current experiments suggest that not all GABA-acting agents produce equivalent profiles of developmental disruption. The case of etomidate is particularly interesting, as the degree to which it induces apoptosis during brain development is unknown.…”
Section: Discussionsupporting
confidence: 57%
“…32 Interestingly, etomidate exposure during the same period (i.e., P4-P6) does not induce long-term alterations in IPSC frequency. 33 Collectively, these data, along with our current experiments suggest that not all GABA-acting agents produce equivalent profiles of developmental disruption. The case of etomidate is particularly interesting, as the degree to which it induces apoptosis during brain development is unknown.…”
Section: Discussionsupporting
confidence: 57%
“…In rat spinal dorsal horn neurons, ET at 10 μmol/L potentiated GABA current and slowed activation, desensitization, and deactivation of GABA A receptors; while ET at 10-1,000 μmol/L directly activated and desensitized GABA A receptors [1]. In hippocampal pyramidal cells, ET slowed the decay time of miniature inhibitory postsynaptic currents kinetics [9]. The ET inhibited thalamocortial relay neurons activity by potentiation of both synaptic and extrasynaptic GABA A receptors [10].…”
Section: Introductionmentioning
confidence: 90%
“…Waterloo et al ( 11 ) found that fracture orthopedic surgery can cause damage to some soft tissues, leading to endothelial cell infiltration, producing inflammatory response; reducing the inflammatory response during operation can significantly increase the success rate of operation and improve the prognosis of patients. Zhang et al ( 12 ) showed that the propofol-induced anesthesia can significantly reduce the inflammatory response of patients during operation, obviously inhibiting the release of inflammatory factors and reducing the infiltration of neutrophils and eosinophils. Postoperative cognitive impairment is a common neurological complication of patients after operation, which often occurs in elderly patients, causing serious damage to the memory, attention and orientation of patients, and even affecting the life quality of patients after operation ( 13 ).…”
Section: Discussionmentioning
confidence: 99%